ANALISIS TATA KELOLA PENGELOLAAN BARANG MILIK DAERAH PADA SEKRETARIAT DPRD KOTA BANDAR LAMPUNG DALAM MEWUJUDKAN AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH - Ediyansyah Ediyansyah; Agus Purnomo (Jurnal Riset Multidisiplin Edukasi, 2026)
Regional Property Management (Barang Milik Daerah/BMD) is a fundamental component of accountable, transparent, and effective public governance. However, the management of regional assets within local government institutions continues to encounter challenges that hinder the optimal utilization of public assets. This study aims to analyze the governance of Regional Property Management at the Secretariat of the Regional House of Representatives (DPRD) of Bandar Lampung City and identify the factors affecting its implementation. This research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and document analysis and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that Regional Property Management has generally been implemented in accordance with the stages of asset management, including planning and budgeting, recording and inventory, utilization and use, safeguarding and maintenance, as well as the implementation of accountability, transparency, and supervision principles. Nevertheless, the implementation has not yet reached an optimal level due to several constraints, including planning that is not fully based on updated asset data, inconsistencies between administrative records and physical asset conditions, suboptimal asset utilization, limited maintenance budgets, inadequate human resource competencies, weak inter-unit coordination, and insufficient integration of asset information and supervision systems. Therefore, strengthening asset management information systems, enhancing the capacity of personnel, improving coordination and supervision, and regularly updating asset data are essential to achieving accountable, transparent, effective, and good governance-oriented regional asset management.